Dampak Pembangunan Sirkuit MotoGp Terhadap Peningkatan Pendapatan UMKM Sektor Pariwisata Di Kuta Mandalika - Lilik Rispita Putri; Farhana Muhammad; Huzain Jailani (Alpatih Harapan Semesta, 2026)
This study also aims to determine and analyze how the MotoGP Circuit development impacts the revenue growth of MSMEs in four main sectors: accommodation, culinary, transportation, and supporting services in the Kuta Mandalika area. This research used a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The research informants were 13 MSMEs from various sectors and one expert informant representing the sub-district head of Pujut Village, Central Lombok. The informant selection technique used purposive sampling, taking into account direct involvement in tourism economic activities around the Mandalika Circuit area. Data were analyzed through data reduction, data presentation, and conclusion drawing using the Milles & Huberman interactive model. The results of this study indicate that the construction of the Mandalika MotoGP Circuit has had a significant positive impact on increasing the revenue of MSMEs in the tourism sector. In the accommodation sector, visitor numbers doubled during the MotoGP event. The culinary sector experienced a surge in sales turnover, particularly for local specialties. The transportation sector also experienced an increase in passengers, while supporting service sectors such as souvenir and woven fabric sellers benefited from the increased demand for MotoGP-themed products and Mandalika icons.